Toward an Understanding of the Madden-Julian Oscillation: With a Mesoscale-Convection-Resolving Model of 0.2 Degree Grid - Masanori Yamasaki (Advances in Meteorology)
This paper describes results from numerical experiments which have been performed as the author's first step toward a better understanding of the Madden-Julian oscillation (MJO). This study uses the author's mesoscale-convection-resolving model that was developed in the 1980s to improve parametrization schemes of moist convection. Results from numerical experiments by changing the SST anomaly in the warm pool area indicate that the period of the MJO does not monotonously change with increasing SST anomaly. Between the two extreme cases (no anomaly and strong anomaly), there is a regime in which the period varies in a wide range from 20 to 60 days. In the case of no warm pool, eastward-propagating Kelvin waves are dominant, whereas in the case of a strong warm pool, it produces a quasi-stationary convective system (with pronounced time variation). In a certain regime between the two extreme cases, convective activities with two different properties are strongly interacted, and the period of oscillations becomes complicated. The properties and behaviors of large-scale convective system (LCS), synoptic-scale convective system (SCS), mesoscale convective system (MCS), and mesoscale convection (MC), which constitute the hierarchical structure of the MJO, are also examined. It is also shown that cloud clusters, which constitute the SCS (such as super cloud cluster SCC), consist of a few MCS, and a new MCS forms to the west of the existing MCS. The northwesterly and southwesterly low-level flows contribute to this feature. In view of recent emphasis of the importance of the relative humidity above the boundary layer, it is shown that the model can simulate convective processes that moisten the atmosphere, and the importance of latent instability (positive CAPE), which is a necessary condition for the wave-CISK, is emphasized.